EVOLUTION OF PUBLIC FINANCIAL ECONOMY IN TERMS OF DIGITALISATION AND E-COMMERCE DEVELOPMENT - Agafoshyn, Vadym (Current Problems of Sustainable Development, 2026)
The article examines the theoretical foundations and conceptual evolution of the public financial economy in the context of digitalisation and the rapid development of e-commerce. The study substantiates a hierarchical approach to understanding this category through the logical sequence “economy → public economy → public finances → public financial economy”, which allows for a consistent disclosure of its institutional and functional characteristics. The evolution of scientific approaches to the interpretation of these categories is analysed within classical political economy, neoclassical welfare theory, Keynesian and post-Keynesian approaches, institutional economics, and contemporary digital economy concepts. Particular attention is devoted to the transformational impact of digitalisation, platformisation, and e-commerce on public finance mechanisms. It is demonstrated that digital technologies fundamentally alter the nature of financial relations by expanding cross-border transactions, transforming tax administration, and increasing the role of digital platforms and data-driven governance in public finance management. The article highlights that traditional fiscal approaches, largely focused on territorially localised economic activity, are becoming insufficient in the context of the global digital economy and the growth of online commercial interactions. Based on a critical analysis of existing theoretical approaches, the author proposes an original definition of the public financial economy as an institutionally organised subsystem of the public economy that encompasses economic relations, financial mechanisms, managerial instruments, and institutional structures aimed at the formation, distribution, and utilisation of public financial resources for the reproduction of public goods and the implementation of state functions. Furthermore, the study systematises the principles governing the functioning of the public financial economy by distinguishing economic, institutional, organisational- managerial, social, and digital-transformational principles. It is concluded that the development of e-commerce and digital governance requires the adaptation of traditional public finance theory to the networked and transnational nature of contemporary economic processes.
Keywords: public financial economy; public finances; public economy; digitalisation; e-commerce; institutional approach; principles of financial governance